Sex dependent influence of a functional polymorphism in steroid 5‐α‐reductase type 2 (SRD5A2) on post‐traumatic stress symptoms123. Issue 3 (15th March 2013) - Gillespie, Charles F.; Almli, Lynn M.; Smith, Alicia K.; Bradley, Bekh; Kerley, Kimberly; Crain, Daniel F.; Mercer, Kristina B.; Weiss, Tamara; Phifer, Justine; Tang, Yilang; Cubells, Joseph F.; Binder, Elisabeth B.; et al.
Abstract A non‐synonymous, single nucleotide polymorphism (SNP) in the gene coding for steroid 5‐α‐reductase type 2 (SRD5A2) is associated with reduced conversion of testosterone to dihydrotestosterone (DHT). Because SRD5A2 participates in the regulation of testosterone and cortisol metabolism, hormones shown to be dysregulated in patients with PTSD, we examined whether the V89L variant (rs523349) influences risk for post‐traumatic stress disorder (PTSD). Study participants (N = 1, 443) were traumatized African‐American patients of low socioeconomic status with high rates of lifetime trauma exposure recruited from the primary care clinics of a large, urban hospital. PTSD symptoms were measured with the post‐traumatic stress symptom scale (PSS). Subjects were genotyped for the V89L variant (rs523349) of SRD5A2. We initially found a significant sex‐dependent effect of genotype in male but not female subjects on symptoms. Associations with PTSD symptoms were confirmed using a separate internal replication sample with identical methods of data analysis, followed by pooled analysis of the combined samples (N = 1, 443, sex × genotype interaction P < 0.002; males: n = 536, P < 0.001). These data support the hypothesis that functional variation within SRD5A2 influences, in a sex‐specific way, the severity of post‐traumatic stress symptoms and risk for diagnosis of PTSD. © 2013 Wiley Periodicals, Inc.